The Use Of Ultrasonography To Detect The Response Of Local Awassi Ewes To Synchronization Of Estrous And Superovulation To Different Intravaginal Progestagen sponge And eCG: K. A. Hussein , S.N. Omran ,H.M. AL-Rawi - Hussein, K. A. (The Iraqi Journal of Veterinary Medicine, 2007)
The aim of this study was to induction of estrous synchronization andsupper ovulation by using intravaginal sponges and injection of different timeand dose of eCG and count the number of corpora lutea and nonovulatedvesicles by using 5MHz ultrasonography in local Awassi ewesThis study were included forty Awassi ewes aged about (3-5) years and 5rams of same breeds. These ewes allotted randomly into five groups (8 ewes foreach group). Ewes of the first four groups were treated with progesteronehormone by using intra vaginal sponges. Saturated with 40 mg of flourogestonAcetate (FGA) for 14 days, while the fifth group was used as a control nottreated with any hormone. Ewes of group 1 and 2 were injected with 500 and750 I.U of eCG. I.M subsequently at time of sponges removal, while ewes ofgroups 3 and 4 were injected with 500 and 750 I.U of eCG I.M subsequentlybefore 48 hrs from sponges removal. The results of the present study showedthat significant difference (P<0.05) in mean of time of estrus after removed ofsponges. The results also showed significant differences (P<0.05) in the lengthof mean of estrus phase between four treated groups. Also the results showedthat the injection of different time were lead to increase in mean of corpora lutialnumber in treated groups, and there was significant difference (P<0.05) inovulation rate.